Stakeholder Mapping in the Management of the Nyaru Menteng Urban Forest Ecotourism Area - Dea Monika Simanjuntak; Nurul Hikmah; Yonatan Ari Santoso (Journal of Public Policy, Governance and Local Government, 2026)
This study identifies and maps the stakeholders involved in managing the Nyaru Menteng Urban Forest Ecotourism Area in Palangka Raya, Central Kalimantan, and examines their relative power and interests in the management process. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observation, documentation, and snowball sampling. Stakeholder mapping was conducted using Bryson's Power versus Interest Grid to classify actors according to their level of influence and concern. The findings identify ten stakeholders with different mandates, capacities, and degrees of involvement. The Central Kalimantan Provincial Forestry Office is positioned as the key player because it holds the formal authority and has a high interest in planning, implementing, supervising, and evaluating the area. Three government agencies are classified as context setters: the Central Kalimantan Provincial Culture and Tourism Office, the Palangka Raya City Tourism, Culture, Youth and Sports Office, and the Central Kalimantan Provincial Public Works and Spatial Planning Office. Six stakeholders are categorized as subjects, namely ecotourism area management officers, the Tumbang Tahai urban village administration, the Batuah Tourism Awareness Group, the local community, the Borneo Orangutan Survival Foundation, and the Bukit Batu Sector Police. No stakeholder is classified as crowd. The mapping shows that management effectiveness depends on stronger inter-agency coordination and greater empowerment of high-interest stakeholders whose formal influence remains limited. A more structured collaboration mechanism is therefore needed to support inclusive and sustainable ecotourism governance.